APOA1 gene polymorphisms in the South Asian immigrant population in the United States - Henkhaus, Rebecca S. (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Coronary artery disease (CAD) is a leading cause of death in the United States. South Asian immigrants (SAIs) from the Indian subcontinent living in the US are disproportionately at higher risk of CAD than other immigrant populations. Unique genetic factors may predispose SAIs to increased risk of developing CAD when adopting a Western lifestyle including a higher-fat diet, more sedentary behavior and additional gene-environment interactions. SAIs are known to have low levels of the protective high density lipoprotein (HDL) and an altered function for Apo-lipoprotein A-1 (ApoA1), the main protein component of HDL cholesterol. One gene that may be genetically distinctive in this population is APOA1 which codes for ApoA-1 protein, a potentially important contributing factor in the development of CAD. MATERIALS AND METHODS: DNA sequencing was performed to determine the status of the seven single-nucleotide polymorphisms (SNPs) in the APOA1 gene from 94 unrelated SAI adults. Genotypes, allelic frequencies, and intragenic linkage disequilibrium of the APOA1 SNPs were calculated. RESULTS: Several polymorphisms and patterns were common among persons of south Asian ethnicity. Frequencies for SNPs T655C, T756C and T1001C were found to be different than those reported in European Caucasian individuals. Linkage disequilibrium was found to be present between most (13 of 15) SNP pairings indicating common inheritance patterns. CONCLUSIONS: SAIs showed variability in the sequence of the APOA1 gene and linkage disequilibrium for most SNPS. This pattern of APOA1 SNPs may contribute to decreased levels of HDL cholesterol reported in SAIs, leading to an increased risk for developing CAD in this population.